Study on the accessibility and affordability of 50 drugs in Wuhan based on the WHO/HAI standardization method - Zuojun Dong; Shaoya Zhang; Shuaijun Wu; Xintong Xie; Guojun Sun; Xuanyao Yu (Frontiers in Public Health, 2023)
ObjectiveTo understand the availability and affordability of essential drugs in Wuhan since the implementation of the national essential medicine system, and to provide a basis for the subsequent formulation and improvement of related policies.MethodsUsing the standard survey method jointly developed by the WHO and Health Action International (HAI), a sample of 50 essential drugs was selected to investigate and evaluate their availability and affordability in public medical and health institutions and social retail pharmacies in Wuhan, using six diseases with high clinical morbidity as the targets.ResultsThe availability of the original drug and the lowest-priced generic drug in public hospitals is 26.4 and 42.47% respectively, and that in retail pharmacies is 26.8 and 54.4% respectively. The median price ratio of the original drug and the lowest-priced generic drug is 28.71 and 2.23 respectively in public hospitals, and 29.24 and 3.59 respectively in retail pharmacies; In addition to individual drugs, such as omeprazole, others are affordable. The availability of essential drugs in public hospitals in Wuhan is lower than that in social retail pharmacies, and the availability of the lowest-priced generic drugs is much higher than that of original drugs.ConclusionThe availability of essential drugs in public hospitals in Wuhan is lower than that in social retail pharmacies, and the availability of the lowest-priced generic drugs is much higher than that of original drugs. The price of the original drug is much higher than the international reference price; The price of medicines in public hospitals is lower than that in retail pharmacies;the overall condition of affordability is good, but there is a big gap between the affordability levels of original drugs and generic drugs, and the affordability of original drugs is relatively poor. It is recommended to adjust the relevant policies according to the actual situation of Wuhan city itself, moderately ensure the supply of original drugs, improve the price transparency of retail pharmacies, and ensure that the basic drug needs of the public are met.